Enumeration and antimicrobial activity of bacterial isolates from undisturbed and contaminated soils in North Macedonia - Kostandinovska, Sofija; Radmanovik, Nikola; Boskovski, Ognen; Kungulovski, Dzoko; Atanasova-Pancevska, Natalija (Macedonian Journal of Ecology and Environment, 2024)
Particularly in temperate regions, seasonal change has an effect on microbial communities directly through climatic function. The microbial populations of an undisturbed and contaminated soil undergo temporal change over the course of four seasons. Eight soil samples were collected from different regions in North Macedonia. The undisturbed soil was collected from mountain Karadzica (protected area Jasen) and the contaminated soil was collected around the factory OHIS, operating in the chemical industry. The samples were collected using sterile bags along with sterile spatula. All the samples were transffered to the Microbiology laboratory, under sterile conditions. Bacillus spp. and Actinobacteria were isolated from the samples using a dillution method, based on the use of heat pretreatment for the isolation of Bacillus spp. and a selective media for the isolation of Actinobacteria. Confirmation was carried out by Gram staining method of all isolates. Soil samples corresponding to the autumnal season showed the greatest number of antimicrobial strains, 30 in total from both regions. Soil pH and moisture contents and as well as the concentration of organic carbon were determined for all soil samples. We found an inverse correlation between the organic carbon content and the number of isolates from undisturbed soil and a positive correlation between the both parameters in contaminated soil. Antimicrobial assays of the isolates were carried out against six bacteria and three fungi, using the agar well diffusion method. Bacillus strains from the undisturbed soil samples showed greater antimicrobial activity against Gram negative test microorganisms from the winter samples, while Bacillus strains from the summer contaminated soil samples demonstrated larger activity. In comparison, Actinobacteria strains demonstrated antagonistic activities only from the autumn season from both samples. The findings of this study show that the relationship between of the microbial communities and their ecosystem depend on the presence of anthropogenic contamination.